2018
DOI: 10.2147/idr.s154328
|View full text |Cite
|
Sign up to set email alerts
|

Skin bacterial flora as a potential risk factor predisposing to late bacterial infection after cross-linked hyaluronic acid gel augmentation

Abstract: IntroductionCross-linked hyaluronic acid (HA) gel is widely used in esthetic medicine. Late bacterial infection (LBI) is a rare, but severe complication after HA augmentation. The aim of this study was to determine whether patients who underwent the HA injection procedure and developed LBI had qualitatively different bacterial flora on the skin compared to patients who underwent the procedure without any complications.MethodsThe study group comprised 10 previously healthy women with recently diagnosed, untreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Two studies did not detect any bacteria in the collected samples [19,33]. The (mainly Staphylococcus epidermidis) and Propionibacterium acnes, which were detected in up to 98% of positive cultures, and which lead to the hypothesis that the presence of these bacteria is involved in development of LIRs [7,8,24,28,31,32]. Two studies compared bacterial presence in samples from patients with adverse events and patient with no adverse events, both finding a much higher rate of bacteria in the adverse events' group [7,24].…”
Section: Discussion Bacterial Contamination and Lirsmentioning
confidence: 99%
“…Two studies did not detect any bacteria in the collected samples [19,33]. The (mainly Staphylococcus epidermidis) and Propionibacterium acnes, which were detected in up to 98% of positive cultures, and which lead to the hypothesis that the presence of these bacteria is involved in development of LIRs [7,8,24,28,31,32]. Two studies compared bacterial presence in samples from patients with adverse events and patient with no adverse events, both finding a much higher rate of bacteria in the adverse events' group [7,24].…”
Section: Discussion Bacterial Contamination and Lirsmentioning
confidence: 99%
“…The observed repellency to VOCs produced by C. koseri may be understood if the natural occurrence of the bacterium is considered: C. koseri is a gram-negative bacillus of the family Enterobacteriaceae commonly found in animal intestines, soils, water, sewage and contaminated food, and it is widely recognized for causing devastating meningitis in neonates and severe infections in immunosuppressed patients [48]. This bacterium is not part of the healthy human skin microbiota; human skin isolations where this bacillus is found are commonly from sick patients [48,49] so that, these volatiles could signal an unhealthy individual to the bugs.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of probiotics into the scheme was justified by the results of our previous study, which showed that treatment with physiological skin flora decreased the risk of LBI after cross-linked HA administration 28. We are aware that our choice of probiotics was not perfect for ensuring an appropriate composition of the physiological skin flora during and after empirical broad-spectrum antibiotic usage.…”
Section: Discussionmentioning
confidence: 99%